2014
DOI: 10.1257/aer.104.5.412
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Race Heterogeneity: The Impact of Students with Limited English on Native Students' Performance

Abstract: Recent evidence suggests that exposure to a larger share of Limited English (LE) students is associated with a slight decline in performance for students at the top of the achievement distribution. In this paper we explore whether LE peer effects differ by gender and race. Utilizing school-by-year fixed effect methods that allow us to address possible endogeneity with respect to the schools students attend, we find evidence of heterogeneous peer effects of LE students on natives. Specifically, we find no LE st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 18 publications
2
19
1
Order By: Relevance
“…Likewise, a recent study demonstrated that ethnic diversity is significantly associated with a messy and disorderly classroom climate (Veerman 2015 ). Potential reasons may include language differences, which may be perceived as worse for a non-immigrant child, if attending a class with more immigrant children, than for an immigrant child, as elaborated in a study by Diette and Uwaifo Oyelere ( 2014 ). Immigrant children might also have experienced a range of traumatic events (i.e., assaults, serious accidents, abuse), which can have a negative impact on their functioning in the classroom (Kataoka et al 2012 ) and may result in a class with more immigrant children being perceived as messier and more disorderly if children are not immigrants themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a recent study demonstrated that ethnic diversity is significantly associated with a messy and disorderly classroom climate (Veerman 2015 ). Potential reasons may include language differences, which may be perceived as worse for a non-immigrant child, if attending a class with more immigrant children, than for an immigrant child, as elaborated in a study by Diette and Uwaifo Oyelere ( 2014 ). Immigrant children might also have experienced a range of traumatic events (i.e., assaults, serious accidents, abuse), which can have a negative impact on their functioning in the classroom (Kataoka et al 2012 ) and may result in a class with more immigrant children being perceived as messier and more disorderly if children are not immigrants themselves.…”
Section: Discussionmentioning
confidence: 99%
“…In the face of these trends, there are concerns that the influx of foreign-born students may adversely impact the educational outcomes of US-born students as well as inducing them to move to private schools where there are fewer immigrant students. Prior studies have reported that foreign-born students "crowd out" natives from colleges and graduate programs (Hoxby 1998;Borjas 2004), while the presence of students with limited English proficiency presents a barrier to other students' learning in US schools (Chin et al 2013;Diette and Uwaifo Oyelere 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although a positive relationship between immigration and USborn students' tendency to move into private schools has been found in the literature, the mechanism driving this native flight is not entirely clear; however, there are a few potential explanations. Recent works have documented that an influx of foreign-born students with limited English proficiency adversely affects native students' performance in math and reading test scores (Chin et al 2013;Diette and Uwaifo Oyelere 2014). Due to this potential effect, native households may respond to the inflow of foreign-born students by enrolling their children in private school.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that inclusion of disadvantaged children in mainstream classrooms exert negative effects on the other learners (e.g. Figlio, 2007;Carrell and Hoekstra, 2010;Cho, 2012;Kristoffersen, 2013;and Diette and Uwaifo Oyelere, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the availability of unique population wide individual level panel data allows us to improve upon the estimation strategy compared to much previous work. Like for instance Fletcher (2009) for children with emotional problems and Cho (2012) and Diette and Uwaifo Oyelere (2014) for English Language Learners (ELL), we employ a value added model which implies that our disruptiveness measure is only required to be exogenous with regards to changes in test scores, not with regards to levels of test scores. However, our strategy does not rely on variation in disruptive classmates within school-grade or within individual.…”
Section: Introductionmentioning
confidence: 99%